CASE REPORT: TRAFFICKING OF A YOUNG FOREIGN LADY (Journal of Forensic Medicine & Toxicology, 2019)
Trafficking in persons is also known as human trafficking or modern slavery is described by US Department of state as the “act of recruiting, harboring, transporting, providing or obtaining a person for compelled labor or commercial sex acts through the use of force, fraud or coercion”. Human trafficking is one of the major problems in India. Till date no concrete study has been conducted so far to know the exact number of trafficked kids in India. The New York Times has reported on the widespread problem of human trafficking in India especially in the state of Jharkhand. Also in the report it is stated that young girls are trafficked from neighboring Nepal to India. The reasons for human trafficking are many, despite 60 years of independence, the benefits of economic development have not trickled down to the marginalized sections of the society and millions of people still live below the poverty line.
Keywords: Trafficking; female trafficking; sexual exploitation of trafficked women